Anti-Hemorrhagic Agents in Oral and Dental Practice: An Update. (October 2013) - Scarano, A.; Murmura, G.; Di Cerbo, A.; Palmieri, B.; Pinchi, V.; Mavriqi, L.; Varvara, G.
Many oral surgeons in their daily practice have the problem of controlling postoperative bleeding. In surgical, oral and maxillofacial practice, standard anti-hemorrhagic protocols, especially in high risk patients, are obviously required and need to be continuously updated. The purpose of this review is to give a rational insight into the management of bleeding in oral and dental practice through modern drugs and medical devices such as lysine analogues and serine protease inhibitors, desmopressin, fibrin sealants, cyanoacrylates, gelatins, collagen and foams, protein concentrates, recombinant factors, complementary and alternative medicine and other compounds.